Age and gender differences in persons with stuttering - Sudhi, Nisha; John, Merin; Y V, Geetha (Journal of All India Institute of Speech and Hearing, 2010)
Gender difference in stuttering is a much talked debated issue. A lot of studies have been done on this, mostly in the western countries. Stuttering is not only reported to be less common in females compared to males, with a 1:4 ratio, but its onset, development and recovery characteristics are more in favour of females. The present study is aimed to explore the similarities and differences in nature of disfluencies, if any, in male and female persons with stuttering, across the age groups in the Indian context. A retrospective analysis of 132 case files of all clients registered with the complaint of stuttering over a period of 6 months was made. The data was analyzed in terms of age of onset, nature and type of onset, associated problems and etiology of stuttering, across the gender and age groups. Across gender, significant differences have been obtained in most of the parameters under study and across the age and within gender too significant findings have been observed. The study confirms many of the earlier findings by other authors with regard to gender differences in stuttering. Female PWS are different in the onset, nature, development, severity characteristics of stuttering compared to male PWS.